ESTRATEGIAS DEL DOWNSIZING EN LAS MAQUILADORAS DE CIUDAD JUÁREZ, CHIHUAHUA, MÉXICO - Aranda, Angélica Quintana; Ramírez, Mirna Liliana Guillén; González, Juan Alberto González; Cuevas- Contreras, Tomas (European Scientific Journal, ESJ, 2012)
This work analyzes the Downsizing, this phenomenon is has positioning in the majority of business due to the economic impacts that has suffered United States has affected the majority of organizations from around the world, businesses and organizations have been implemented this strategy as a resource for optimization within the organization. The entrepreneur industry, which is the primary source of employment in the major border areas with United States, has resorted to this practice strategic due to the low demand of its customers, discusses the concept, the impact on the entrepreneur industry sector and the strategies used by applies of Downsizing.